Testing mediation in cross-legged panel designs - Buško, Vesna (Array, 2007)
Mediation has been defined as the process or mechanism by which an intervening mediator variable (M) carries the eff ect of an independent variable (X) to a dependent variable (Y). Methodological literature gives an extensive account of the statistical approaches to the analysis mediation and different methods for assessing the magnitude and significance of indirect effects. Mediation effects are typically quantified as the product of the path coefficient linking X to mediator M and the coefficient linking M to Y while controlling for X. Differences among the methods pertain mainly to the problem of how to assess the significance of this quantity. As mediation is by definition a causal process, testing indirect effects hypothesis against cross-sectional data may be misleading. Panel designs off er means to correct for the related problems. A structural equation model used to demonstrate this strategy for testing mediation was specifi ed within a 2-wave cross-lagged panel design, with stationarity assumed on theoretical grounds. The empirical data used for this purpose were based on the follow-up study on the processes of coping with low-control stress. The results are compared with those obtained by structural equation analyses performed within diff erent methodological framework but tested against the same data sets. These include structural equation models specified in line with the assumptions of latent state-trait theory (LST ; Steyer et al., 1992, 1999), and using the true change modeling procedures.